Bilateral rotatory subluxation of the scaphoid. Issue 2 (June 1994) - Kidney, D D; McCarthy, G; Ryan, J; Plunkett, P K
Abstract : We describe the case of a 17-year-old girl, who presented to our Accident and Emergency (A&E) department following minor trauma to her forearm. Initial x-rays were misread as normal. Radiographs demonstrated classical features of rotatory subluxation of the scaphoid, which was found to be bilateral.